Development of a Numerical Model for the Formation of Complete and Incomplete Channel Blockages and Their Influences on River Flow - Takashi Wada; Hiroshi Miwa; Naoto Aoki; Yusei Fujii (Journal of the Civil Engineering Forum, 2025)
Large landslides, triggered by torrential rain or earthquakes, can slide down mountainous slopes and block river channels at the lower end of the slopes. In cases where the landslide volume is relatively small compared to the river discharge, or when the distance between the landslide slope and the river channel is long, incomplete channel blockages may occur due to an insufficient supply of landslide material to fully block the river flow. Since the shape of the channel blockage is the final result obtained through the temporal changes in landslide material movement, river flow, and topography, considering their interactions, it is necessary to investigate the blockage shape by numerical analysis that accounts for these interactions. Therefore, we developed a numerical model to predict the formation of various channel blockages by incorporating the combined conditions of topography, landslide volume, and river discharge. The developed model is a two-dimensional (2-D) model, which can connect several one-dimensional calculation areas for mountainous streams at any selected point in the 2-D area. In addition, the model can consider landslide material movements represented by cylindrical blocks. To verify our model and identify appropriate values for the associated parameters, we investigated the MAE (mean absolute error) for the deposit thickness distribution and the PWO (percentage of the area where the actual and calculated waterlogged areas overlapped) between the actual and calculated results using our model for two previous channel blockages of different sizes. Although our model and the associated parameters still need to be improved by considering the loss of landslide material, they are useful for estimating the magnitude and area of damage caused by large-scale landslides and the associated channel blockage and waterlogging in various river channels with steep side slopes. The calculated results can be utilized in investigating disaster countermeasures for landslides in the area.